Hubungan Kebijakan Dividen (Dividend Yield Dan Dividend Payout Ratio) Terhadap Volatilitas Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Fahmawati, Asiska Ayu, Drs. Ma'ruf, MM (2017)
This research was conducted with the aim to analyze the effect of dividend policy against the volatility of stock prices at the manufacturing companies listed on the Indonesia stock exchange (BEI) in the period 2012-2014. In this study using a sample taken with purposive sampling method with the specified criteria. Such data using time series and cross section data often referred to by the panel. The data used manufacturing company in 2012-2014 from IDX registered in BEI. Analytical tools used in this research is a classic assumption test and regression analysis. The results showed that the variables have a significant influence against the volatility of stock prices is just the dividend payout ratio. And control variables that influence the company's profit is significant volatility (Earning Volatility), company size (Size), and Company Growth (Growth). All three negative effect.